Association Study of Fecundity Gene BMPR1B with Prolificacy in Surti Goats under Farm and Field Condition - Dangar, NS; Pandya, GM; Ramani, UV; Padheriya, YD; Sangma, T; Patel, SS; Devkatte, S (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The Surti is a dual purpose goat breed of Gujarat. The bone morphogenetic protein receptor type 1B (BMPR1B) gene of transforming  growth factor beta (TGF-β) superfamily ligands is playing a role in ovulation as well as litter size. Mutation in Exon-6 region of BMPR1B  gene with base size 190 bp reported increasing litter size. Based on the known mutation information in goat and sheep, PCR primers  were designed to screen polymorphism in total 100 Surti goats, 50 Surti goats from University Farm, Navsari and 50 Surti goats from  field units of Southern part of Gujarat. During PCR-RFLP study no polymorphic sites were found for Exon-6 region of BMPR1B on Surti  goats. Moreover, the twinning rate was 10% in first parity and higher in subsequent second (62.5%) and third (76.8%) parties.
Keywords: Fecundity gene; Polymorphism; BMPR1B; PCR-RFLP; Surti goat